2021
DOI: 10.3389/fmars.2021.631757
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment and Management Challenges of Key Rural Human Health Infrastructure Under Sea Level Rise

Abstract: Accelerating sea level rise in Virginia, United States, will significantly increase the flooding threat to low-lying roads, residences, and critical infrastructure as well as raise the water table, allowing saltwater intrusion into well water and threatening the function of septic fields. Although most of the adaptation work in Virginia has focused on urban economic centers, the majority of the coastline is rural and faces different threats and opportunities to address them compared to urban areas due to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Groundwater supplies high concentrations of NH 4 + (∼200 μM) to the GP‐STE, likely due to remineralization of organic matter during transport to the coast or contamination resulting from septic leakage (Mitchell et al., 2021). Schutte et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater supplies high concentrations of NH 4 + (∼200 μM) to the GP‐STE, likely due to remineralization of organic matter during transport to the coast or contamination resulting from septic leakage (Mitchell et al., 2021). Schutte et al.…”
Section: Discussionmentioning
confidence: 99%
“…+ (∼200 μM) to the GP-STE, likely due to remineralization of organic matter during transport to the coast or contamination resulting from septic leakage (Mitchell et al, 2021). Schutte et al (2017) reported similar NH 4 + concentrations with depth on Sapelo Island, GA, USA, but other east coast sites such as Waquoit Bay, MA, USA observe NO 3 − rich groundwater (Spiteri, Slomp, Charette et al, 2008;Talbot et al, 2003).…”
Section: Groundwater Supplies High Concentrations Of Nhmentioning
confidence: 95%
“…Our study shows that total road inaccessibility in the low elevation coastal communities of Chesapeake Bay, Virginia, will increase rapidly with rising water levels. High tide flooding has increased around 125% in the Southeast Atlantic since 2000 (Sweet et al, 2018) and related flood impacts to infrastructure are predicted to increase at an accelerated rate with sea level rise (Mitchell et al, 2021). The comparison of road length flooded versus road length inaccessible suggested that inaccessible road length averaged twice the length of the flooded road.…”
Section: Discussionmentioning
confidence: 99%
“…They can be combined with other vulnerability analyses to consider the effects of multiple stressors on the low coastal zone communities. Flooding in low elevation coastal zones does not happen within a vacuum; sea level rise-driven impacts to wastewater and drinking water infrastructure are co-occurring in rural areas (Mitchell et al, 2021). Together these stressors may change the trajectory of the economy or recommend different adaptation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in lake water levels may lead to a corresponding increase in the landward groundwater table elevation, and thereby reduce the vertical separation between septic tile beds and groundwater table. This can be a concern as it then limits the efficiency of the septic tile bed in attenuating wastewater constituents including nutrients (Mitchell et al, 2021). Based on groundwater levels measured at PZ-1 (x = 71 m), there was ~ 1 m increase in the groundwater table between 2014-2015 and 2020 (Figure 1c).…”
Section: Change In Hydrological Conditions Between Sampling Periodsmentioning
confidence: 99%